Proteínas del plasma y grupos sanguíneos ABO y Rh del gorrión común (Passer domesticus) en dos localidades de Costa Rica - Reynolds, Jenny (1982)
The house sparrow (Passer domesticus) invaded Costa Rica in 1974 or early 1975 and is now established throughout the country in ecologically varied areas. Four plasma proteins: transferrin, ceruloplasmin, haptoglobin and albumin, and the blood groups of the ABO and Rh systems were studied in two populations from two ecologically different localities: Santa Cruz (54 m), Guanacaste Province and Cartago (1440 m), Cartago Province. Five different electrophoretic patterns were obtained for transferrin implying the presence of at least three segregating alleles in both populations. These were present in both localities, with pattern 1 predominating in Cartago (44%) and pattern 4 in Santa Cruz (35%). The other three (Hp, Alb, Cer) were monomorphic. Individuals belonging to the AB blood group (66%) and Rh- (85%) predominated in both localities. This genetic structure is probably determined by the migratory behavior, the colonization system of the species, the effective population size and random processes. Possible modes of adaptation of this group in Costa Rica are discussed.